In-fiber liquid-level probe based on Michelson interferometer via dual-mode elliptical multilayer-core fiber. Issue 13 (19th July 2016) - Liang, Xiao; Ren, Guobin; Li, Yang; Liu, Zhibo; Wei, Huai; Jian, Shuisheng
Abstract: An in-fiber liquid-level probe fabricated from homemade dual-mode elliptical multilayer-core fiber (EMCF) was proposed and experimentally demonstrated. The proposed sensor simply consists of a segment of the EMCF with one end coated with silver film, and a Michelson interferometer is roughly established when light from single-mode fiber incident from the other end. The detected interference patterns, rather clean due to the few-mode property, shift as the liquid level due to strong interaction between high-order modes and measurands through evanescent waves. Both the propagation characteristics and operation principle of such a sensor were demonstrated in detail, and sensitivities of 33.48, 43.35, and 48.93 pm/mm corresponding to liquid indices of 1.333, 1.353, and 1.373 were successfully achieved with a 50-mm EMCF probe, respectively. Moreover, the proposed sensor had the potential to discriminate measurand index after proper calibration.